The Influence of Empowerment and Compensation Towards The Work Productivity of Nurse and Midwife in The Faisal Islamic Hospital of Makassar - Indriyani, Dian (International Journal of Psychosocial Rehabilitation, 2020)
— Labor productivity is an issue that should receive serious attention from the hospital, because increase in labor productivity will not happen by itself, but there should be effort and participation from both the hospital and from the employees themselves. The purpose of this study was to analyze the influence of empowerment and compensation on the productivity of nurses and midwives working in hospitals Islam Faisal Makassar. The kind of research used is analytic survey with cross sectional study samples studied is the entirety of the amount of the studied population numbering 130 people. The analysis was conducted with the Structural Equation Modeling (SEM). The results showed that there was no effect of empowerment on the productivity of nurses and midwives with a t-value = 1:09 (1:09 <1.96) caused due to condition of each individual in which every individual has their own opinion about empowerment, and there is influence between compensation and productivity of nurses and midwives in hospitals Islam Faisal Makassar with t-value of 2:33 (2:33> 1.96). So that the compensation perceived by the respondent or another employee will continue to represent an increase in productivity. Based on two variables that have more influence to work productivity of nurses and midwives is compensated. Should the implementation of empowerment and good compensation to nurses and midwives in order to increase the productivity of nurses and midwives.